Differential expression of matrix metalloproteinases and miRNAs in the metastasis of oral squamous cell carcinoma - Zhen-Hu Ren; Kun Wu; Rong Yang; Zhe-Qi Liu; Wei Cao (BMC, 2020)
Abstract Background Our study aimed to reveal the regulatory mechanisms of miRNAs and matrix metalloproteinases (MMPs) in oral squamous cell carcinoma (OSCC). Methods The mRNA and miRNA expression profiles of six metastatic tumour samples, six nonmetastatic tumour samples, and six normal tissue samples were used for microarray analysis. Moreover, the important genes and miRNAs were validated by published profiles in Oncomine and by qRT-PCR. Results MMP7, MMP13, and MMP10 were upregulated, and MMP12 and MMP9 were downregulated in metastatic tumours compared with nonmetastatic tumours. MMP7 was regulated by miR-4697-5p and miR-7109-5p. MMP7 and MMP13 were upregulated in OSCC samples compared with normal samples in Oncomine. Moreover, qRT-PCR revealed that the expression of miR-7109-5p and miR-34b was decreased in metastatic tumours compared with nonmetastatic tumours. Conclusions Our study suggested that miR-7109-5p and miR-34b might play important roles in the metastasis of OSCC by regulating MMP7 and MMP13 expression, respectively.